Organ donation in Germany: opt-in vs. opt-out—opinions and voting patterns in the 19th German Bundestag - Zeybek, Asli; Le, Nguyen-Son; Settmacher, Utz; Koch, Martina; Arbogast, Helmut; Ziganshyna, Svitlana; Hahnenkamp, Klaus; Nashan, Björn (Frontiers in Transplantation, 2025)
In early 2024, 8,394 patients were waitlisted for solid organ transplantation in Germany. Long waiting times and declining donor numbers highlight the urgency for political measures to improve the organ donation system. This retrospective analysis examined the attitudes of the 19th German Bundestag members towards organ donation and their voting behavior on the opt-out system, which was decided on January 6, 2020. The results were analyzed in relation to party affiliation, age, gender, and educational background. Among members of parliament (MP), 34% were in favor for organ donation, 8% were critical, and 58% made no statement on organ donation at all. Younger members were less likely to express an opinion than older ones (p < 0.001). CDU/CSU (50%) and members of the SPD (48%) showed the highest approval, while The Green Party (39%) showed the lowest approval rate. AfD members had the highest abstention rate (96%, p < 0.001). SPD (66%, OR 33.24) and CDU/CSU (63%, OR 28.32) strongly supported the opt-out system, while AfD (94%) and The Green Party (88%) strongly rejected. Overwhelming majorities of the AfD (94%), The Green Party (89%), and FDP (81%) members who had not previously expressed an opinion to organ donation and legislation voted against the opt-out system, whereas majorities of SPD (66%) and CDU/CSU (66%) voted in favor. Most members who held opposing views on organ donation voted against the opt-out solution. Party affiliation was strongly correlated with both attitudes towards organ donation and voting behavior as well as a considerable lack of in-depth knowledge regarding transplant legislation. A fact-based discussion involving medical professionals, who play a key role in the organ donation process, is essential, along with a thorough understanding of the organ transplant law.